Notary Role In The Process Of Establishment Of Foreign Investment Company Limited Statutory Company Limited In The City Kendari - Dewa Bayu Lumanga; Amin Purnawan (Jurnal Akta, 2020)
The purpose of this research are: 1) To analyzing role notary in the process of establishment of foreign investment limited liability company under the laws of a limited liability company in Kendari. 2) To analyzing obstacles is facing a notary in the process of establishment of the Foreign Investment Limited Liability Company under the laws of a limited liability company in Kendari and provide solutions to these obstacles. The method used by researchers is empirical approach juridical law and specification in this study were included descriptive analysis. As for sources and types of data in this study are primary data obtained from field studies with interview Notary in Kendari. And secondary data obtained from the results of research studies that literature. Based on The role of the Notary In Process Incorporation Limited Liability Investment Asing based on Act of Company Limited in Kendari is providing legal advice and pouring the will of the parties to the deed of incorporation in order to not conflict with existing regulations and is responsible for ensuring the deed of incorporation approved by the Minister of Justice and Rights Human Rights of the Republic of Indonesia, and once approved, the deed of establishment is the highest law for limited liability companies and limited liability company and a binding third party. Barriers Faced Notary In Process Incorporation Limited Liability Based on the Foreign Investment Limited Liability Company Act in Kendari is: a) Business Licensing; b) domicile Enterprises; c) Determination Business Sector; d) Administrative requirements; e) Capital To Establish Company. The solution is: a) It helps if you first understand your business; b) In selecting the business domicile you should use the designation of the building is for the business; c) In such case, please see the business field closest correlation with the idea; d) In person at the local PTSP to determine the current terms to provide a solution establishing businesses; e) Learn first line of business you will run.Keywords: Role; Notary; Incorporation; Limited Liability Company (PT); Foreign Direct Investment (FDI)